The dynamics of technical economic indicators of crop and animal production in South-East region - Lidia Iurchevici; Rodica Chetroiu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
The South-East Region represents the joining place of Moldova, Muntenia and Dobrogea, situated, thus, at the confluence of the history and national culture. The administrative structure of the region includes six counties: Constanta, Tulcea, Braila, Galati, Vrancea and Buzau. Being the second largest in the 8 regions of Romania, covers 35,762 km2, ie 15% of total national area. Agriculture holds an important share in the region economy, 40.4% of the population of region being occupied in this sector. The work studies the evolution, during 2000 - 2010, of the following technical and economic indicators specific to agriculture in South-East: the land fund, material and technical basis of agriculture, agricultural crop area and production, average production for the main crops, livestock and animal production, the number of animals per 100 ha, value of agricultural production, agricultural production indices. It shows that the total agricultural area of South-East Region met an upward curve in the first three years of the interval, decreasing slightly from the base year. Of total cultivated areas, cereals represented in 2010, 62.6% and 99.8% of the surface cultivated with cereals in 2000. The surfaces of the private sector, cultivated with cereals, increased in 2010 by 18.4% compared to 2000. Of the total cereals, wheat and corn represent over 90%, the rest being represented by other straw cereals. Among animal products, a positive dynamic in the analyzed period, have registered the pork meat, the sheep and goat's milk, wool, eggs and honey. The value of agricultural production in 2009 was 140% higher than the initial.
Keywords: 330; land fund; agricultural area; production; cereals; dynamic